SAGE: Novel Therapy to Reduce Inflammation in a Naturally Occurring-Dog Model of Periodontal Disease - Raja V; Gu Y; Lee HM; Deng J; Prestwich G; Ryan M (Dove Medical Press, 2022)
Veena Raja,1 Ying Gu,2 Hsi-Ming Lee,1 Jie Deng,1 Glenn Prestwich,3,4 Maria Ryan5 1Department of Oral Biology and Pathology, Stony Brook School of Dental Medicine, Stony Brook, NY, USA; 2Department of General Dentistry, Stony Brook School of Dental Medicine, Stony Brook, NY, USA; 3Department of Medicinal Chemistry, The University of Utah, Salt Lake City, UT, USA; 4Health Sciences Spokane, Washington State University, Spokane, WA, USA; 5Colgate and Palmolive Company, Piscataway, NJ, USACorrespondence: Veena Raja, Department of Oral Biology and Pathology, School of Dental medicine, Stony Brook University, Stony Brook, NY, 11794-8706, USA, Tel +1 516-813-6250, Fax +1 631 632-9705, Email veenaraja18@gmail.comObjective: To determine the effect of a semi-synthetic-glycosaminoglycan Ether (SAGE) as a universal therapeutic benefit to reduce periodontal inflammation and alveolar bone loss in naturally occurring-beagle-dog model of periodontal disease as a surrogate for human non-risk associated natural periodontitis.Methods: Six adult female dogs with generalized periodontitis were distributed into two groups: control and SAGE treatment (n=3/group). After a 1-hour full-mouth scaling and root planning (SRP) at baseline, control or SAGE treatment (50mg/mL) bioadhesive gel formulation was locally applied for 12 weeks. Various clinical periodontal measurements (probing depth, CAL) were measured at different time periods (baseline, 4, 8 and 12 weeks), and gingival crevicular fluid (GCF), blood samples and gingival tissue biopsies (12 week) were analyzed for inflammatory mediators, collagenases and cell-signaling molecules. Standardized radiographs were taken at baseline and 12week period.Results: SAGE treatment significantly reduced gingival inflammation (GCF flow), pocket depth (PD), and clinical attachment loss (CAL) compared to control. SAGE also considerably reduced alveolar bone loss and reduced MMP-9, IL-6, CRP levels in gingival tissue, GCF and plasma. Cell-signaling molecules in the inflammatory cascade system TLR-2, TLR-4, p38 MAPK, ERK1/2 and NF-kB responded to SAGE in a pattern consistent with reductions at the active phase of the inflammatory process and collagenolysis.Conclusion: In the beagle dog model of periodontitis, local SAGE administration significantly attenuated clinical measures of periodontitis, pro-inflammatory cytokines, MMPs, and signal transduction molecules. All our studies, using in vitro and in vivo models, support the therapeutic potential of SAGE as an innovative adjunct to SRP in the treatment of chronic periodontal disease.Keywords: periodontitis, bone loss, matrix metalloproteinases, inflammation, semi-synthetic-sulfated polysaccharide